Pengaruh Budaya Organisasi, Komunikasi Organisasi, dan Lingkungan Kerja Terhadap Work Engagement di Kantor Sekretariat Daerah Kota Salatiga - Muhammad, Faaza Asykar; Rahmaningtyas, Wisudani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This research aims to discuss the impact of organizational culture, organizational communication, and work environment toward work engagement at Sekretariat Daerah Kota Salatiga. This research uses quantitative research. Data is collected through questionnaires and interviews. This research involved 149 respondents so the sampling technique used was saturated. Next, data was collected through multiple linear regression analysis using SPSS program. The research shows that there is a significant relationship between organizational culture, organizational communication, and work environment towards work engagement on employee. This finding indicates the need for attention to employees to improve work engagement. Therefore, this study is expected to be a reference for agencies in managing human resources in the agency environment.